THE ROLE OF NEUROMEDIATORS AT PERIMENOPAUSAL SYNDROME - Sherbina, I.N. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
The research of 60 women of the overmenopausal period was done. The level of gonadotrophic hormones, dophamine, serotonine was researched. The rabe of the clinical symptoms was evaluated. The results of the researches let think that there is an important role of hypersecretion of neuromediators in the pathogenesis of the neuro- and psychological disoders of perimenopausal syndrome.